Amelogenin “Nanorods” Formation During Proteolysis by Mmp-20 - Yang, Xiudong (2011)
Amelogenin is cleaved by enamelysin (Mmp-20) soon after its secretion, and the cleavage products accumulate in specific locations during enamel formation, suggesting that parent amelogenin proteolysis is necessary for activating its functions. To investigate the precise roles of Mmp-20 and its influence on the assembly of amelogenin, an in vitro enzymatic digestion process mimicking the initial stages of amelogenin proteolysis was investigated at near-physiological conditions using recombinant porcine amelogenin (rP172) and enamelysin. Hierarchically organized nanorod structures formed during different digestion stages were detected by TEM. At the earliest stage, uniformly dispersed parent amelogenin spherical particles, mixed with some darker stained smaller spheres, and accompanying elongated chain-like nanostructures were observed. Cylindrical nanorods, which appeared to be the result of tight assembly of thin subunit cylindrical discs with thicknesses ranging from ~2.5 nm to ~6.0 nm, were formed after an hour of proteolysis. These subunit building blocks stacked to form nanorods with maximum length of ~100 nm. With the production of more cleavage products, additional morphologies spontaneously evolved from the cylindrical nanorods. Larger ball-like aggregates ultimately formed at the end of proteolysis. The uniform spherical particles, nanorods, morphological patterns evolved from nanorods, and globular aggregated microstructures were successively formed by means of co-assembly of amelogenin and its cleavage products during a comparatively slow proteolysis process. We propose that, following the C-terminal cleavage of amelogenin, co-assembly with its fragments leads to formation of nanorod structures whose properties eventually dictate the super-structural organization of enamel matrix, controlling the elongated growth of enamel apatite crystals.